2017
DOI: 10.1038/ncomms13935
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of human PCNA sliding on DNA

Abstract: Sliding clamps encircle DNA and tether polymerases and other factors to the genomic template. However, the molecular mechanism of clamp sliding on DNA is unknown. Using crystallography, NMR and molecular dynamics simulations, here we show that the human clamp PCNA recognizes DNA through a double patch of basic residues within the ring channel, arranged in a right-hand spiral that matches the pitch of B-DNA. We propose that PCNA slides by tracking the DNA backbone via a ‘cogwheel' mechanism based on short-lived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
111
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 46 publications
12
111
2
Order By: Relevance
“…NMR studies and molecular dynamics simulations revealed that the lysines walk along successive backbone phosphates of one DNA strand during sliding [8], and predict a sliding rate far faster than the DNA polymerase, consistent with single-molecule measurements of rapid clamp diffusion on DNA [10]. The fast rate of clamp diffusion on DNA ensures that it will not hinder the DNA polymerase rate.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…NMR studies and molecular dynamics simulations revealed that the lysines walk along successive backbone phosphates of one DNA strand during sliding [8], and predict a sliding rate far faster than the DNA polymerase, consistent with single-molecule measurements of rapid clamp diffusion on DNA [10]. The fast rate of clamp diffusion on DNA ensures that it will not hinder the DNA polymerase rate.…”
mentioning
confidence: 73%
“…A recent study [8] has illuminated the clamp sliding process along DNA and the findings are fascinating. A crystal structure of human PCNA encircling a 10 base pair duplex DNA has been solved to high resolution, and the architecture of the clamp–DNA interface is now clear (Figure 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations